MLCK and PKC Involvements via Gi and Rho A Protein in Contraction by the Electrical Field Stimulation in Feline Esophageal Smooth Muscle - Park, Sun Young (The Korean Physiological Society and The Korean Society of Pharmacology, 2010)
We have shown that myosin light chain kinase (MLCK) was required for the off-contraction in response to the electrical field stimulation (EFS) of feline esophageal smooth muscle. In this study, we investigated whether protein kinase C (PKC) may require the on-contraction in response to EFS using feline esophageal smooth muscle. The contractions were recorded using an isometric force transducer. On-contraction occurred in the presence of N(G)-nitro-L-arginine methyl ester (L-NAME), suggesting that nitric oxide acts as an inhibitory mediator in smooth muscle. The excitatory composition of both contractions was cholinergic dependent which was blocked by tetrodotoxin or atropine. The on-contraction was abolished in Ca(2+)-free buffer but reappeared in normal Ca(2+)-containing buffer indicating that the contraction was Ca(2+) dependent. 4-aminopyridine (4-AP), voltage-dependent K(+) channel blocker, significantly enhanced on-contraction. Aluminum fluoride (a G-protein activator) increased on-contraction. Pertussis toxin (a G(i) inactivator) and C3 exoenzyme (a rhoA inactivator) significantly decreased on-contraction suggesting that Gi or rhoA protein may be related with Ca(2+) and K(+) channel. ML-9, a MLCK inhibitor, significantly inhibited on-contraction, and chelerythrine (PKC inhibitor) affected on the contraction. These results suggest that endogenous cholinergic contractions activated directly by low-frequency EFS may be mediated by Ca(2+), and G proteins, such as Gi and rhoA, which resulted in the activation of MLCK, and PKC to produce the contraction in feline distal esophageal smooth muscle.